KEEFEKTIFAN Beauveria bassiana DAN Spicaria sp. TERHADAP KEPIK RENDA LADA Diconocoris hewetti (DIST.) (HEMIPTERA: TINGIDAE) - I. M. Trisawa; I W. Laba (Pusat Penelitian dan Pengembangan Perkebunan, 2006)
Effectiveness of Beauveria bassiana and Spicaria sp. to Pepper Lace Bug, Diconocoris hewetti (Dist.) (Hemiptera: Tingidae)The experiment was conducted in la-boratory and in the field, Research Assesment of Agricultural Technology, Bangka Belitung Province, since November to December 2004. The objective of this experiment to find out effectiveness Beauveria bassiana and Spicaria sp. to adult of pepper lace bug, Diconocoris hewetti. Three type of B. bassiana were used, they are ED2, ED3, and ED6. The concentra-tion of laboratory experiment were used 1 g/l and 10 g/l for each strain. Beside of pathogen fungi also used Nimbo 0.3 AS, bota-nical insecticide as treatment check and water as control. The experiment was arange with Randomized Completely Design with 10 treat-ments and 4 replications in laboratory, while in the field was used Randomozed Block De-sign with 8 treatments and 4 replication. The treatment of field experiment based on the laboratory test result. The result indicated that B. Bassiana and Spicaria sp. effective to control of D. hewetti in laboratory and in the field. The highest mortality in laboratory are 93.33% on B. bassiana treatment with ED2 strain and 10 g/l concentrations. Strain of ED2 and ED6 with 10 g/l concentrations for each treatment indi-cated that 97.50% of the mortality in the field experiment. Spicaria sp. able to kill D. hewetti but the level of mortality lower than B. Bas-siana namely 16.67% till 9 days after appli-cation